Malaysia`s labour force participation in rural and urban areas - Mohd Nor, Nor Amna A’liah; Said, Rusmawati (Asian Economic and Social Society, 2014)
In Malaysia, transformation of economic structure from agricultural sector to manufacturing and services sector has led to urbanization process in which individual migrates from rural to urban areas for better jobs opportunity and higher wages. This inclination of movement has led to a reduction in labour absorption and expands the labour force disparities between urban and rural areas. In light of these disparities, this study used Labour Force Survey (LFS) data from Malaysia Department of Statistic to examine the determinants and changes between rural and urban labour force participation in Malaysia. The results of logistic regression models demonstrate that age group 25-34 years are the main determinant of rural and urban labour force participation. However, the probability of household in urban areas participate in labour market are higher than rural areas. Educations in urban areas are more significant compared to rural areas. A non-linear decomposition exhibits that the observed rural and urban differentials are attributable to differences in endowment (explained variables).